Dynamics of Citizenship in the Era of Globalization: Challenges and Opportunities - Zahwa Salsabila Ginting (International Journal of Students Education, 2024)
In the era of globalization like now this all something experience dynamics and development towards digital, incl citizenship in Indonesia. Globalization be marked with exists dependency and openness between one country to another . Anxiety digital citizenship in the industrial era 4.0 is proof that rate globalization accelerated by digital technology and making all over the world increasingly connected . Utilization development of the digital world in context citizenship is one of way that can be done as effort answer identical developments over time with progress technology information . Study This aim For know challenges and opportunities for the country in the Industrial Era 4.0 and knowing developments over time with increasingly technology progress and develop. Method used in study This is study literature (library research ). This study using secondary data form journal scientific, results study as well as books and other relevant sources. Data analysis techniques used covers three stages that is organizing, synthesizing, and identifying. Research result this show that openness information and global connectivity creates challenge new, esp related with digital citizenship and participation political via online platforms. Challenge the involve complexity in respond fast change technology, protection privacy in digital space, and adaptation identity national in face current globalization is not limited. However, in the middle dynamics this is also available opportunity significant for utilise technology as means For increase participation citizen for protect privacy , and building identity strong national.